Determinasi Kompetensi Manajerial Kepala Sekolah, Supervisi Akademik, Etos Kerja, dan Motivasi Kerja terhadap Kinerja Guru SMK Teknologi Nasional di Era Revolusi Industri 4.0 - Ardiyasa, I Made Peri; Yudana, I Made; Dantes, Kadek Rihendra (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study is to determine the amount of determination of the principal's managerial competence, academic supervision, work ethic and work motivation on the performance of teachers of SMK Teknologi Nasional. This type of research is expost facto with a sample of 36 teachers. Data was collected by questionnaire. Data analysis was performed by simple regression techniques, multiple regression and partial correlation. The results showed that: 1) there was a significant determination of the principal's managerial competence on teacher performance with a coefficient of determination of 0.991 and an effective contribution of 22.62%. 2) There is a significant determination of academic supervision of teacher performance with a coefficient of determination of 0.984 and an effective contribution of 23.62%. 3) There is a significant determination of work ethic on teacher performance with a coefficient of determination of 0.993 and an effective contribution of 26.78%. 4) There is a significant determination of work motivation on teacher performance with a coefficient of determination of 0.986 and an effective contribution of 26.81%. 5) simultaneously, there is a significant determination of the principal's managerial competence, academic supervision, work ethic, and work motivation on teacher performance with a coefficient of determination of 0.998 on the performance of teachers of SMK Teknologi Nasional. Thus, these four variables are used as predictors of the level of tendency to improve the performance of teachers of SMK Teknologi Nasional.